The Impact of Interventions that Integrate Accelerometers on Physical Activity and Weight Loss: A Systematic Review. Issue 1 (26th August 2016) - Goode, Adam P.; Hall, Katherine S.; Batch, Bryan C.; Huffman, Kim M.; Hastings, S. Nicole; Allen, Kelli D.; Shaw, Ryan J.; Kanach, Frances A.; McDuffie, Jennifer R.; Kosinski, Andrzej S.; Williams, John W.; Gierisch, Jennifer M.
Abstract: Background: Regular physical activity is important for improving and maintaining health, but sedentary behavior is difficult to change. Providing objective, real-time feedback on physical activity with wearable motion-sensing technologies (activity monitors) may be a promising, scalable strategy to increase physical activity or decrease weight. Purpose: We synthesized the literature on the use of wearable activity monitors for improving physical activity and weight-related outcomes and evaluated moderating factors that may have an impact on effectiveness. Methods: We searched five databases from January 2000 to January 2015 for peer-reviewed, English-language randomized controlled trials among adults. Random-effects models were used to produce standardized mean differences (SMDs) for physical activity outcomes and mean differences (MDs) for weight outcomes. Heterogeneity was measured with I 2 . Results: Fourteen trials (2972 total participants) met eligibility criteria; accelerometers were used in all trials. Twelve trials examined accelerometer interventions for increasing physical activity. A small significant effect was found for increasing physical activity (SMD 0.26; 95 % CI 0.04 to 0.49; I 2 = 64.7 %). Intervention duration was the only moderator found to significantly explain high heterogeneity for physical activity. Eleven trials examined the effects of accelerometer interventions on weight. Pooled estimates showed a small significant effect for weight loss (MD −1.65 kg; 95 % CI −3.03 to −0.28; I 2 = 81 %), and no moderators were significant. Conclusions: Accelerometers demonstrated small positive effects on physical activity and weight loss. The small sample sizes with moderate to high heterogeneity in the current studies limit the conclusions that may be drawn. Future studies should focus on how best to integrate accelerometers with other strategies to increase physical activity and weight loss.